THE IMPLEMENTATION OF HADHANAH THEORY ON INDONESIAN CHILDREN RIGHTS PROTECTION - Iman Jauhari (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Child’s custody in Islamic Law is stated in 38 Surahs and 79 Verses of Koran concerning to children rights. Children are both blessings and mandates from Allah, The Almighty, of whom we must take a good care due to the values, rights, and dignity they have as a member of human race. Children rights are also essential parts of Human Rights which is regulated on The 1945 Constitution of The Republic of Indonesia, under Article 28 B Paragraph (2) as amended by the Second Amendment of 2000. It is stated that, “Every child shall have the right to live, to grow and to develop, and shall have the right to protection from violence and discrimination.”